Child and Adolescent Resilience: Strategies for Coping with Challenges and Stress Systematic Review - Irma Suryani Sulaeman; Fadhilah Ahmad Qaniah; Khusnul Khatimah (PSYCHONESIA: JOURNAL OF PSYCHOLOGY, 2026)
Resiliensi merupakan kemampuan individu untuk beradaptasi dan pulih kembali dari pengalaman traumatis atau stressful. Pada anak dan remaja, resiliensi memainkan peran crucial dalam perkembangan psikologis yang sehat dan kemampuan menghadapi berbagai tantangan hidup. Penelitian ini bertujuan untuk mengidentifikasi dan menganalisis strategi-strategi yang dapat meningkatkan resiliensi anak dan remaja melalui kajian literatur sistematis. Kajian literatur ini menggunakan pendekatan systematic review dengan menganalisis 25 artikel dari berbagai database akademik yang dipublikasikan antara tahun 2010-2024. Artikel dipilih berdasarkan kriteria: (1) fokus pada resiliensi anak dan remaja usia 6-18 tahun, (2) menyajikan strategi atau intervensi resiliensi, (3) publikasi dalam jurnal peer-reviewed, dan (4) metodologi penelitian yang robust. Analisis menunjukkan bahwa resiliensi anak dan remaja dipengaruhi oleh enam kategori utama: (1) Faktor individual (self-efficacy, emotional regulation, cognitive flexibility), (2) Faktor keluarga (parenting style, family cohesion, communication patterns), (3) Faktor sekolah (teacher support, peer relationships, school climate), (4) Faktor komunitas (social support, cultural values, community resources), (5) Strategi coping (problem-focused, emotion-focused, meaning-making), dan (6) Program intervensi (skill-building, therapy-based, preventive programs). Resiliensi anak dan remaja bersifat multidimensional dan dapat dikembangkan melalui intervensi yang tepat. Pemahaman komprehensif terhadap faktor-faktor ini penting untuk mengembangkan program yang efektif guna meningkatkan resiliensi dan kesehatan mental anak dan remaja. Kata kunci: Resiliensi, Anak, Remaja, Systematic Literature Review   Abstract Resilience refers to an individual's ability to adapt and recover from traumatic or stressful experiences. In children and adolescents, resilience plays a crucial role in healthy psychological development and the ability to face various life challenges. This study aims to identify and analyze strategies that can enhance resilience in children and adolescents through a systematic literature review. This literature review uses a systematic review approach by analyzing 25 articles from various academic databases published between 2010-2024. Articles were selected based on criteria: (1) focus on resilience in children and adolescents aged 6-18 years, (2) presenting resilience strategies or interventions, (3) publication in peer-reviewed journals, and (4) robust research methodology. The analysis shows that resilience in children and adolescents is influenced by six main categories: (1) Individual factors (self-efficacy, emotional regulation, cognitive flexibility), (2) Family factors (parenting style, family cohesion, communication patterns), (3) School factors (teacher support, peer relationships, school climate), (4) Community factors (social support, cultural values, community resources), (5) Coping strategies (problem-focused, emotion-focused, meaning-making), and (6) Intervention programs (skill-building, therapy-based, preventive programs). Resilience in children and adolescents is multidimensional and can be developed through appropriate interventions. A comprehensive understanding of these factors is essential for developing effective programs to enhance resilience and mental health in children and adolescents.   Keywords: Resilience, Child, Adolescence, Systematic Literature Review